Image and text in the service of the Absolute. Medieval manuscript and the idea of total work of art - Prałat, Emilian (Poznańskie Studia Slawistyczne, 2012)
The article takes up the problem of the medieval manuscript as an example of a total work of art. Miniature painting is an example of diffusional transmittance of the various semiotic orders, which define each other and lead to the creation of a reflection of divine beauty and harmony. The text also refers to the problem of iconoclasm. Historical material from the South Slavic area shows the art of cultural borderlands, where elements based on the principle of pars pro to to are reflected in miniature painting. The intersemiotic research tradition is presented synthetically.